Meeting needs through beggary: an empirical study of the use of begging proceeds in Ibadan North L.G.A. Oyo state, Nigeria (2013)
Begging is a global phenomenon and is one of the most conspicuous features of modern cities in developed and underdeveloped countries of the world. The incidence, and magnitude of the challenges it poses differ from place to place. In Nigeria, with a high poverty rate, the social practice of begging has become so complex that the understanding of its full ramification is now considered central to eradicating it. This study, investigated and documented the functions and pattern of use of begging proceeds among beggars in Ibadan. The Functionalist Theory was used as a theoretical springboard while a descriptive qualitative research design was adopted to guide the investigation. Primary data were generated through 19 In-depth and 2 Key Informant Interviews. Additional information was obtained through Observation. The study- population was drawn from two purposively selected areas in Ibadan North Local Government Area, Bodija and Sabo, where begging activities were common. Participants included beggars, money-handlers, shop owners and traders. Data were interpreted through content analysis, and sometimes reported through direct quotation. The study- showed that beggars depend on proceeds to satisfy socio-economic and psycho-social needs at three crucial levels: the individual, household and aspirational levels. Begging proceeds do not only provide day to day survival for beggars but also assist them in performing minor social roles and in satisfying higher economic and religious goals. The study concluded that the uses of proceeds would remain central to understanding why anti-begging policies have had limited success. It therefore recommends that needs considerations should feature more in strategies designed to control beggary among Nigerians.